Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure, let's solve the equation step by step:
Given equation:
[tex]\[ (w - 4)^2 = 2w^2 + w + 30 \][/tex]
1. First, expand the left-hand side of the equation:
[tex]\[ (w - 4)^2 = w^2 - 8w + 16 \][/tex]
So, our equation becomes:
[tex]\[ w^2 - 8w + 16 = 2w^2 + w + 30 \][/tex]
2. To set the equation to zero, move all the terms to one side. Subtract [tex]\(2w^2 + w + 30\)[/tex] from both sides:
[tex]\[ w^2 - 8w + 16 - 2w^2 - w - 30 = 0 \][/tex]
Combine like terms:
[tex]\[ w^2 - 2w^2 - 8w - w + 16 - 30 = 0 \][/tex]
[tex]\[ -w^2 - 9w - 14 = 0 \][/tex]
3. Multiply the entire equation by -1 to make the leading coefficient positive:
[tex]\[ w^2 + 9w + 14 = 0 \][/tex]
Now, we have a standard quadratic equation:
[tex]\[ w^2 + 9w + 14 = 0 \][/tex]
4. Solve the quadratic equation using the quadratic formula [tex]\((w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a})\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 9\)[/tex], and [tex]\(c = 14\)[/tex].
First, calculate the discriminant:
[tex]\[ b^2 - 4ac = 9^2 - 4 \cdot 1 \cdot 14 = 81 - 56 = 25 \][/tex]
5. Now, apply the quadratic formula:
[tex]\[ w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{-9 \pm \sqrt{25}}{2 \cdot 1} \][/tex]
[tex]\[ w = \frac{-9 \pm 5}{2} \][/tex]
This gives us two solutions:
[tex]\[ w = \frac{-9 + 5}{2} = \frac{-4}{2} = -2 \][/tex]
[tex]\[ w = \frac{-9 - 5}{2} = \frac{-14}{2} = -7 \][/tex]
Therefore, the solutions are:
[tex]\[ w = -2 \quad \text{and} \quad w = -7 \][/tex]
Given equation:
[tex]\[ (w - 4)^2 = 2w^2 + w + 30 \][/tex]
1. First, expand the left-hand side of the equation:
[tex]\[ (w - 4)^2 = w^2 - 8w + 16 \][/tex]
So, our equation becomes:
[tex]\[ w^2 - 8w + 16 = 2w^2 + w + 30 \][/tex]
2. To set the equation to zero, move all the terms to one side. Subtract [tex]\(2w^2 + w + 30\)[/tex] from both sides:
[tex]\[ w^2 - 8w + 16 - 2w^2 - w - 30 = 0 \][/tex]
Combine like terms:
[tex]\[ w^2 - 2w^2 - 8w - w + 16 - 30 = 0 \][/tex]
[tex]\[ -w^2 - 9w - 14 = 0 \][/tex]
3. Multiply the entire equation by -1 to make the leading coefficient positive:
[tex]\[ w^2 + 9w + 14 = 0 \][/tex]
Now, we have a standard quadratic equation:
[tex]\[ w^2 + 9w + 14 = 0 \][/tex]
4. Solve the quadratic equation using the quadratic formula [tex]\((w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a})\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 9\)[/tex], and [tex]\(c = 14\)[/tex].
First, calculate the discriminant:
[tex]\[ b^2 - 4ac = 9^2 - 4 \cdot 1 \cdot 14 = 81 - 56 = 25 \][/tex]
5. Now, apply the quadratic formula:
[tex]\[ w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{-9 \pm \sqrt{25}}{2 \cdot 1} \][/tex]
[tex]\[ w = \frac{-9 \pm 5}{2} \][/tex]
This gives us two solutions:
[tex]\[ w = \frac{-9 + 5}{2} = \frac{-4}{2} = -2 \][/tex]
[tex]\[ w = \frac{-9 - 5}{2} = \frac{-14}{2} = -7 \][/tex]
Therefore, the solutions are:
[tex]\[ w = -2 \quad \text{and} \quad w = -7 \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.